2017
DOI: 10.3390/ijms18061119
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Scavenger Properties against Oxidative and Nitrosative Stress: Impact on Gamete Handling and In Vitro Embryo Production in Humans and Other Mammals

Abstract: Oxidative and nitrosative stress are common problems when handling gametes in vitro. In vitro development in mammalian embryos is highly affected by culture conditions, especially by reactive oxygen species (ROS) and reactive nitrogen species (RNS), because their absence or overproduction causes embryo arrest and changes in gene expression. Melatonin in gamete co-incubation during in vitro fertilization (IVF) has deleterious or positive effects, depending on the concentration used in the culture medium, demons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 129 publications
2
51
0
3
Order By: Relevance
“…DNA methylation states are altered by in vitro culture conditions of preimplantation stage rabbit embryos . In agreement with a previous study, we found that embryos cultured in vitro control group exhibited higher 5‐mC levels than those in vivo. When embryos were cultured in oviduct fluid in vitro, we observed relatively lower 5‐mC levels than those of embryos cultured in vitro control group, indicating that oviduct fluid plays an important role in embryonic epigenetic modifications.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…DNA methylation states are altered by in vitro culture conditions of preimplantation stage rabbit embryos . In agreement with a previous study, we found that embryos cultured in vitro control group exhibited higher 5‐mC levels than those in vivo. When embryos were cultured in oviduct fluid in vitro, we observed relatively lower 5‐mC levels than those of embryos cultured in vitro control group, indicating that oviduct fluid plays an important role in embryonic epigenetic modifications.…”
Section: Discussionsupporting
confidence: 92%
“…Normal embryonic development is disrupted under extremely high ROS levels, which can lead to mitochondria, cell membrane, and DNA damage as well abnormal gene expression . In this study, embryos cultured in vitro control group exhibited higher ROS levels than those in in vivo, which is consistent with a previous report . Notably, we found that embryos cultured in oviduct fluid in vitro exhibited relatively lower levels of ROS than those cultured in vitro control group, suggesting that oviduct fluid has an antioxidant capacity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, this research would contribute not only with basic knowledge but also with practical applications in the field of animal breeding. Melatonin has the potential for improving IVF and other assisted reproductive techniques involving capacitating treatments [28,33]. However, melatonin is also very interesting as a supplement for sperm storage media [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In the early pregnancy, ROS inhibits progesterone production from corpus luteal cells causes Manuscript to be reviewed luteal CL regression [21], and also induces ovarian cell apoptosis [22]. As a potent antioxidant, melatonin detoxifies ROS including OH -, O 2and H 2 O 2 and reduces the oxidative damage of ovarian cells [23] and thus, improves the fertility and fecundity of sheep by improving the survival rate of corpus luteum and embryos [24]. Numerous studies have proved that melatonin promotes the development of oocytes and embryos in sheep [25], pigs [26], cattle [27], mice [28] and humans [29] in the in vitro environment by scavenging ROS or.…”
Section: Discussionmentioning
confidence: 99%